Analisis Pengaruh Upah Minimum Provinsi, Tingkat Pengangguran, dan Harapan Lama Sekolah Terhadap Kemiskinan di Pulau Jawa - Alendra Akbar Widyanto; Ruth Eviana Hutabarat (CV. Ulil Albab Corp, 2024)
Poverty is still an important issue that requires resolution. This study seeks to determine the effect of provincial minimum wage, open unemployment rate, and expected years of schooling on the poverty rate in Java. The secondary data used in this study were obtained from the Central Bureau of Statistics. This research technique uses quantitative methods and is analyzed using panel data regression with a fixed effect model. The results of this study indicate that the provincial minimum wage and expected years of schooling have a significant effect on poverty in Java, while the unemployment rate has no effect on poverty in Java.